2023
DOI: 10.1111/ene.16098
|View full text |Cite
|
Sign up to set email alerts
|

Effect of efgartigimod on muscle group subdomains in participants with generalized myasthenia gravis: post hoc analyses of the phase 3 pivotal ADAPT study

Vera Bril,
James F. Howard,
Chafic Karam
et al.

Abstract: Background and purposeGeneralized myasthenia gravis (gMG) is a rare, chronic, neuromuscular autoimmune disease mediated by pathogenic immunoglobulin G (IgG) autoantibodies. Patients with gMG experience debilitating muscle weakness, resulting in impaired mobility, speech, swallowing, vision and respiratory function. Efgartigimod is a human IgG1 antibody Fc fragment engineered for increased binding affinity to neonatal Fc receptor. The neonatal Fc receptor blockade by efgartigimod competitively inhibits endogeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
(58 reference statements)
1
2
0
Order By: Relevance
“…However, substantial relief from long-term diplopia and external ophthalmoplegia highlights the necessity of considering not just clinical measurements but also symptomatic relief affecting the patients’ QOL, such as extraocular muscle palsy [ 25 ]. This finding aligns with that reported previously, suggesting that efgartigimod treatment notably improves ocular symptoms in patients with MG [ 26 ]. Similarly, Case 4 underscores the drug’s potential in managing bulbar symptoms.…”
Section: Discussionsupporting
confidence: 93%
“…However, substantial relief from long-term diplopia and external ophthalmoplegia highlights the necessity of considering not just clinical measurements but also symptomatic relief affecting the patients’ QOL, such as extraocular muscle palsy [ 25 ]. This finding aligns with that reported previously, suggesting that efgartigimod treatment notably improves ocular symptoms in patients with MG [ 26 ]. Similarly, Case 4 underscores the drug’s potential in managing bulbar symptoms.…”
Section: Discussionsupporting
confidence: 93%
“…About 68 % of those in the efgartigimod group were MG-ADL responders, with an odds ratio of 4.95, compared to placebo group. Primary and post hoc analyses of ADAPT trials both demonstrated greater improvements were seen across MG-ADL and QMG in efgartigimod group [ 1 , 2 ]. These improvements and reductions of IgG were typically observed over 1 to 2 weeks after the first infusion.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical benefits of efgartigimod are durable and tolerable, with most adverse events being mild to moderate [ 1 ]. Furthermore, efgartigimod provides consistent clinical improvements of muscle function and strength across all muscle groups [ 2 ]. Efgartigimod is also called as “plasma exchange in a bottle” [ 3 ].…”
Section: Introductionmentioning
confidence: 99%